The Comparing Self-Efficacy and Responsibility-Taking in Couples with and without Family Conflicts - Ojaghi, Maryam; Narimani, Mohammad (IJRDO - Journal of Social Science and Humanities Research, 2019)
This study was conducted to compare the self-efficacy and responsibility-taking in families going through divorce and normal families. The research method was scientific-comparative. The research population included normal individuals and individuals going through divorce. The research sample included 50 individuals going through divorce and 50 normal individuals, and the individuals going through divorce were chosen through simple random sampling by referring to the family courts and Dispute Settlement Councils. Subsequently, the normal individuals were also chosen through simple random sampling and matched with the other group for comparison. In order to study and collect data, the following questionnaires were used: 1. Sherer and Adams Self-Efficacy Scale 2. Responsibility Attitudes Scale. The collected data was analyzed by MANOVA. The findings suggested that self-efficacy had a significant difference in individuals going through divorce and normal individuals in all aspects at 0.05. However, there was no significant difference observed in the component of responsibility-taking in individuals going through divorce and normal individuals. Hence, the research results indicate that the individuals going through divorce have lower self-efficacy and higher marital conflicts. Hence, due to creating conflict situations in the family system, whole these issues could interfere with the increase in the risk towards gaining pleasure by the normal marital duties.